AN ENHANCED POWER ANALYSIS OF 35 KWP ON GRID ROOFTOP PLTS IN THE ADMIN BUILDING OF PT. PLN INDONESIA POWER PLTU PANGKALAN SUSU - Muhammad Rizki; Solly Aryza; Hermansyah Alam (Jurnal Scientia, 2023)
PLTS is an alternative in meeting the needs of electrical energy, in which electrical energy is obtained from the photovoltaic process. That is the process of converting energy from sunlight into electrical energy. In its application, many PLTS are built on the roofs of office buildings and houses, which are commonly referred to as rooftop PLTS. In this study, we will discuss the analysis of the power of PLTS rooftop on the grid in order to determine the ability of PLTS to produce electrical energy. This research was conducted in the admin building of PT. PLN Indonesia Power PLTU Pangkalan Susu, Tanjung Pasir Village, Pangkalan Susu Sub-district, Langkat Regency, North Sumatra on Saturday 27 May to 28 May 2023, starting at 08:30 - 17:00 WIB. The highest power loss on 2 monitoring days occurred at 12:00 -13:00 WIB, which was in the range of 1, 800 Wh to 2,200 Wh. It can be seen that the On-grid Rooftop PLTS is unstable because it is heavily influenced by weather conditions. and the intensity of sunlight, therefore, according to the working principle of PLTS On grid, share the load with PLN electricity.